Land Acquisition Problems Project for Electrical Infrastructure Development - Perdana, Adi Pitra; Rohman, Mohammad Arif (Institut Teknologi Sepuluh Nopember, 2020)
The land is a critical resource for infrastructure development. However, land acquisition was still as the biggest problem in realizing infrastructure development in Indonesia. Electricity project is one of the infrastructure projects strategic and needs to be realizing in a short period. Effort at investigating the factors causing a problem in land acquisition for electricity infrastructure projects through an empirical method in Indonesia received scant attention. Therefore, the purpose of this study is to identify and critically assess the factors causing land acquisition problem for electricity infrastructure development using an empirical approach. The study adopted literature review and questionnaire survey. Literature review was using to identify the factors causing in land acquisition problem, which was using to design the questionnaire survey culminating in data analysis. In order to capture a broad perception, the questionnaires were administered to three different primary stakeholder groups comprised consultants, project owner and government. Data collected were analysed using mean score. The study revealed the mean score ranking of 24 identified factors causing in land acquisition problem for electrical infrastructure development. Five highest problems in land acquisition projects are (1) A project has not integrated with City Plan; (2) The part of land that is not acquired cannot be utilized by the owner; (3) Inventory data is not accurate; (4) Poor stakeholders coordination; (5) Differences interpretation of land acquisition regulations.